Dapatkah Pembayaran Jasa Lingkungan Mencegah Deforestasi dan Meningkatkan Kesejahteraan Masyarakat? Pelajaran dari Hutan Desa Laman Satong, Kabupaten Ketapang, Kalimantan Barat - Nugroho, Cahyo; Supriatna, Jatna; Kusworo, Ahmad (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
In order to reduce deforestation, the Government of Indonesia has introduced several initiativies, including a Hutan Desa (village forest) program to bring local communities to become actor in the forest management. The Reduced Emissions from Deforestation and Forest Degradation plus (REDD+) and Payment for Environmental Services (PES) scheme for the hutan desa is one of the alternative scheme to provide economic incentives for their effort to manage their forest sustainably. This study aims to evaluate the impact of the initiation of REDD+ and PES funds for hutan desa to deforestation and community wellbeing. The impact to deforestation is measured through quantitative approach by comparing quantitatively forest cover on 1070ha of village forest through satelite image analysis. The impact to community wellbeing is measured through participatory wellbeing assessment involving 30 informants during a focus group discussion. An attribution to the variables are conducted qualitatively by in-depth interviews to 25 key informants. The result shows eventhough the benefit provided by the initiation of REDD+ and PES (the money) is much less than the opportunity cost, the community is still accepting the scheme and succeeds reducing deforestation. However, the benefit is not sufficient enough yet to improve community wellbeing.